Thinking Systemically About Multi-Agency Collaboration – Organising Against Organised Crime - Brocklesby, John (School of Management Working Papers, 2011)
Reflecting a philosophy of „joined-up‟, „holistic‟, or „integrated‟ government, multiagency collaborative partnerships are now a common mechanism for public service delivery in areas of social concern that span two or more departmental jurisdictions. Typically these partnerships exist in ill-defined and complex social problem areas such as crime, housing, poverty and child abuse. The paper seeks to demonstrate how, in face of a multitude of organisational challenges, harnessing the various components of service delivery to act coherently in addressing complex problems requires a commensurate way of thinking, namely one that is appropriately holistic and systemic. Using the example of the changing nature of transnational organised crime, the paper seeks to demonstrate how issues and problems that are arising with recent law enforcement collaborative arrangements can be investigated through whole-of-system mapping and debate.